The Enigma of Bioactivity and Toxicity of Botanical Oils for Skin Care - Moore, Erin M.; Wagner, Charles; Komarnytsky, Slavko (Frontiers in Pharmacology, 2020)
Botanical oils have a long history of traditional use and are routinely applied to skin care. The focus of this review is to contrast the functionality of skin oils versus the differential biological and toxicological effects of major plant oils, and to correlate them to their compositional changes. In total, over 70 vegetable oils were clustered according to their lipid composition to promote awareness of health practitioners and botanical product manufacturers for the safety and efficacy of oil-based interventions based on their fatty acid profiles. Since multiple skin disorders result in depletion or disturbance of skin lipids, a tailored mixture of multiple botanical oils to simultaneously maintain natural skin-barrier function, promote repair and regeneration of wounded tissues, and achieve corrective modulation of immune disorders may be required. As bioactive constituents of botanical oils enter the human body by oral or topical application and often accumulate in measurable blood concentrations, there is also a critical need for monitoring their hazardous effects to reduce the possible over-added toxicity and promote maximal normal tissue sparing. The review also provides a useful tool to improve efficacy and functionality of fatty acid profiles in cosmetic applications.